Secondary attachment and mental health in Pakistani and Scottish adolescents: A moderated mediation model. (29th April 2020) - Imran, Somia; MacBeth, Angus; Quayle, Ethel; Chan, Stella W.Y.
Abstract : Objectives: Research into adolescent mental health has tended to focus on primary attachment relationships. However, the effect of secondary attachment relationships and the role of culture remain under‐explored. This study examined the associations between primary attachment, secondary attachment, and coping strategies (task‐focused, emotion‐focused, and avoidant coping) with psychological well‐being and psychological distress in adolescents across two cultural settings. Design: A cross‐sectional study. Method: An identical test battery was used across two geographic sites in Pakistan ( N = 510; 12–18 years; 51.5% male; mean age = 14.50) and Scotland ( N = 610; 12–18 years; 53.6% male; mean age = 13.97). Associations were tested separately in each sample using moderated mediation modelling for the outcome variables: psychological well‐being and psychological distress. Results: For psychological well‐being, all three coping strategies were significant partial mediators and secondary attachment was a significant moderator in both samples. Secondary attachment moderated the association between emotion‐focused coping and psychological well‐being in the Pakistani sample only. For psychological distress, task‐focused coping was a significant full mediator in the Pakistani sample only. In contrast, for the Scottish sample, task‐focused coping and emotion‐focused coping were significant partial mediators. Secondary attachment's direct effect on psychological distress was significant in both samples. Secondary attachment also moderated the association between emotion‐focused coping and psychological distress in the Pakistani sample only. Conclusions: The cross‐cultural evidence suggests that alongside primary attachment, it is important to target secondary attachment through coping strategies, in order to enhance psychological well‐being and lessen psychological distress in adolescents. Practitioner points: Secondary attachment plays a different role from primary attachment in adolescents. Therefore, it is important to target both primary attachment and secondary attachment security to enhance psychological well‐being and lessen psychological distress. Cross‐cultural differences in coping suggest that differential strategies to target different coping dimensions may enhance adolescent well‐being across cultures. These cross‐cultural differences highlight the ethical importance of cultural sensitivity among clinicians working with adolescents globally.